IMPLEMENTASI MODEL ROLE PLAYING UNTUK MENINGKATKAN SELF CONFIDENCE PESERTA DIDIK MATERI ”INDONESIAKU KAYA BUDAYA” KELAS IV SDN 198/I PASAR BARU - Indah Maya Sari; Ahmad Hariandi; Khoirunnisa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is a classroom action research (CAR) using the Role Playing learning model aimed at seeing the process of increasing self-confidence of fourth grade students at SDN 198/I Pasar Baru. The research process began with observation, interviews and documentation. Based on the results of the study, Role Playing was able to increase students' self-confidence in learning the IPS material of Indonesiaku is rich in culture. This is because students experienced an increase in self-confidence by looking at the self-confidence indicators that can be seen from each cycle. The results obtained by students' self-confidence in cycle 1 meeting I were 43.63% with a sufficient category and meeting II was 53.89% with a fairly high category. In cycle II, meeting I increased to 68.31% with a high category and meeting II increased by 83.05% with a very high category.